Conocimiento sobre sexualidad en adolescentes del Colegio Emiliano Ortega Espinoza - Remache Cueva, Liliana de los Angeles (2015)
The sexuality is a natural characteristic of all the human beings that develops during the whole life, from before being born even, the death is determined by a series of biological, psychological, social, cultural and spiritual aspects that determine the form of behavior or of sexual conduct of every person. The present investigation that takes as a target to identify the knowledge on sexuality that there have the adolescents of the School Emiliano Ortega Espinoza del Cantón Catamayo of the Province of Loja. The investigation is of descriptive type – quantitative the universe was formed 1450 students, the sample was constituted by 435 adolescents that it belongs to 30 % of the population between men and women. For the compilation of the information I use the survey and as I arrange a previously prepared questions questionnaire that one applied to the adolescents in study the obtained results determine that the adolescents possess knowledge of the anatomy of the sexual organs both masculine and femininely. Likewise the investigation shows that the adolescents of both sexes do not know on the physiology of the masculine reproductive device and unlike the physical changes both the man and the woman they know of these and how they are presenting before themselves in its body in the period of the puberty. KEYWORDS: Sexuality, Adolescents, Knowledge, masculine reproductive device; feminine.